2021
DOI: 10.1242/jcs.244152
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel Bax–Cdk1 signalling complex that links activation of the mitotic checkpoint to apoptosis

Abstract: In eucaryotes entry into and exit from mitosis is regulated, respectively, by the transient activation and inactivation of Cdk1. Taxol, an anti-microtubule anti-cancer drug, prevents microtubule-kinetochore attachments to induce Spindle Assembly Checkpoint (SAC, also known as the Mitotic Checkpoint)-activated mitotic arrest. SAC activation causes mitotic arrest by chronically activating Cdk1. One consequence of prolonged Cdk1 activation is cell death. However, the cytoplasmic signal(s) that link SAC activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…As a result of the present study, we constructed a 6-gene pyroptosis-related signature, including BAK1, CASP5, CASP6, GPX4, GZMA, and CHMP4C. Notably, six genes involved in this signature have been implicated in apoptotic pathways as well (Li et al, 2015;Skotte et al, 2017;Wu et al, 2019;Zhou et al, 2020;Darweesh et al, 2021;Ding et al, 2021). Following apoptotic signals, caspase 8 and caspase 3 initiate pyroptosis by processing GSDMC and GSDME, respectively (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the present study, we constructed a 6-gene pyroptosis-related signature, including BAK1, CASP5, CASP6, GPX4, GZMA, and CHMP4C. Notably, six genes involved in this signature have been implicated in apoptotic pathways as well (Li et al, 2015;Skotte et al, 2017;Wu et al, 2019;Zhou et al, 2020;Darweesh et al, 2021;Ding et al, 2021). Following apoptotic signals, caspase 8 and caspase 3 initiate pyroptosis by processing GSDMC and GSDME, respectively (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these CDK1 substrates, BCL2 apoptosis regulator (BCL2), BCL2 apoptosis regulator like 1 (BCL2L1), and dynamin 1 Like (DRP1) are phosphorylated by CDK1, mediating mitochondrial fusion and apoptosis in human cancer cells [114][115][116][117][118][119][120][121] . F-box protein 28 (FBXO28) and carboxypeptidase D (CPD) are phosphorylated by CDK1 increasing ubiquitylation promoting tumorigenesis.…”
Section: Cdk1 Tumor Promotor Substratesmentioning
confidence: 99%
“…Activation of BAX and BAK1 are actually thought to be the last BCL2 family members involved in the events promoting apoptosis execution in mitosis. However, recently it has been suggested that they are not simply effectors waiting for upstream signals to be integrated, but that they play an active role in mitotic cell death by facilitating CDK1 mediated phosphorylation of pro-survival proteins (34). BAX, and to a lesser degree BAK1, appear to be able to interact with CDK1, targeting it to the outer mitochondrial membrane, where it can phosphorylate BCL2 and BCLX to facilitate apoptosis (34).…”
Section: Mitotic Arrest and Apoptosismentioning
confidence: 99%